Beyond organic matter: the world of soil carbon. Issue 6 (5th December 2019) - Straathof, Angela
Abstract : Organic matter (OM) is perhaps the best and most routinely measured indicator of a soil's capacity to support yields and sustain net benefit agroecosystem services. But OM is a broad‐brush measurement; total OM between soil types can vary in its quality. This article explores this variability as well as what, when, and how to measure OM. Earn 0.5 CEUs in Soil & Water Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/704 .